Long‐term evaluation of urinary copper excretion and non‐caeruloplasmin associated copper in Wilson disease patients under medical treatment. Issue 2 (11th February 2019) - Pfeiffenberger, Jan; Lohse, Christine Marie; Gotthardt, Daniel; Rupp, Christian; Weiler, Markus; Teufel, Ulrike; Weiss, Karl Heinz; Gauss, Annika
Abstract: Objective: Urinary copper excretion rates and non‐caeruloplasmin associated copper concentrations are increased in patients with Wilson disease. However, there is little literature describing the monitoring of these parameters over the long term. Methods: This is a monocentric retrospective study including data collected between 2003 and 2015 from 321 patients with Wilson disease by chart review. The patients were under therapy with D‐penicillamine, trientine, or zinc. 24‐h urinary copper excretion rates, non‐caeruloplasmin associated copper, and total serum copper concentrations were determined at the start of therapy, as well as 6, 12, 18, 24, 36, and ≥ 60 months after the start of therapy. For patients taking chelating agents, all parameters were measured while under continued therapy, as well as after a 48‐h dose interruption. A mathematical formula to predict 24‐h urinary copper excretion rates under different therapies was established. Results: In all treatment groups, urinary copper excretion rates decreased over time, but the inter‐individual variation of the results was high. Non‐caeruloplasmin associated copper concentrations tended to decline over time, but with a higher variation of results than that observed for urinary copper excretion rates. Conclusion: Due to their variability, urinary copper excretion rates and serum copper concentrations are less than ideal parameters by which to monitor the benefit of a copper‐reducing therapy. Urinary copper excretion rates seem to be more suitable than non‐caeruloplasmin associated copper concentrations for this purpose.